Theater for and with babies: (in)definitions, historical context and characteristics (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Theatre for and with babies is a relatively new field in the Portuguese landscape. Its interdisciplinary nature grounds it in different areas, still in the process of defining itself in both theory and practice, and it falls within a broader concept of Theatre for Children and Youth. Addressing designations internationally assigned to theatre directed at babies and young children, this article aims to provide historical context and explain its characteristics in relation to different dramaturgical formats, scenic and artistic resources, and the specificities of the actor/performer's work.
Keywords: theater for and with babies; theater for childhood and youth; post-dramatic theater